Financing Export Transactions – Logistic Aspects (Economic and Political Thought, 2012)
The article is aimed at demonstrating financial instruments used inforeign trade transactions, including especially those that let an importer becredited by an exporter, and also at assessing them from the point of view ofan exporter. The author also tries to justify the role of logistics not only atthe stage of a transaction implementation but also at the stage of negotiatingthe contract details, including payment issues.Firstly, she discusses financial instruments that are most frequently usedin foreign trade transactions. These are also assessed against a criterionof payment certainty and the protection of the importer’s interests. Next,the author points out the essential logistic conditions for selected ways ofpayment and she analyzes issues of risk management in export transactions,especially types of risk connected with financing a transaction, crediting animporter or guaranteeing payment.The publication also contains a synthetic analysis of conditions for exportfinancing strategies on two selected European markets.